Exploring Library Users’ Perceptions of Librarian Attitudes and Service Performance in Tangerang Regency - Desi Fitriani (CV Media Inti Teknologi, 2025)
Background: Library services play a crucial role in facilitating access to information and supporting learning activities. The interaction between librarians and users determines the quality of service provided. A positive librarian attitude characterized by friendliness, attentiveness, and professionalism can enhance user satisfaction and encourage library utilization. Aims: This study aims to explore the attitudes of librarians in providing services at the Tangerang Regency Library and Archives Office and to understand how users perceive these attitudes. Methods: A qualitative descriptive approach was used, involving three users selected through purposive sampling. Data were collected through observation and interviews, and analyzed using the Miles and Huberman model, which consists of data reduction, data presentation, and conclusion drawing.Results: The findings show that library utilization from 2022–2023 reached an average of 136,270 visitors, with the highest percentage in 2023. Users perceive librarians as generally friendly, polite, and responsive in carrying out their duties. However, some users noted that librarians are not always proactive in offering assistance, particularly in locating collections, and tend to wait for users to ask for help. These attitudes influence users’ overall experience and shape their perceptions of library services. Conclusion: Overall, librarians at the Tangerang Regency Library and Archives Office demonstrate positive service attitudes, including politeness, good communication, and willingness to assist. Nevertheless, improvements are needed in proactive engagement and attentiveness to user needs. Enhancing these aspects may further strengthen user satisfaction and support the library’s role as an effective information and learning resource.